2020
DOI: 10.1111/apt.15700
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: increasing burden of nonalcoholic fatty liver disease—a call to action

Abstract: LINKED CONTENT This article is linked to Estes et al papers. To view these articles, visit https://doi.org/10.1111/apt.15673 and https://doi.org/10.1111/apt.15718.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This is also supported by a recent FibroScan‐based study by Eris et al, which similarly reported NAFLD as the leading etiology of liver fibrosis at their center 26 . It is important to highlight as NAFLD can continue to contribute to liver disease progression in patients with other etiologies of CLD, which have been adequately treated 10,27–29 . Notably, NAFLD‐associated HCC is also markedly on the rise, concurrent with the rise in prevalence of NAFLD 30 .…”
Section: Discussionmentioning
confidence: 69%
“…This is also supported by a recent FibroScan‐based study by Eris et al, which similarly reported NAFLD as the leading etiology of liver fibrosis at their center 26 . It is important to highlight as NAFLD can continue to contribute to liver disease progression in patients with other etiologies of CLD, which have been adequately treated 10,27–29 . Notably, NAFLD‐associated HCC is also markedly on the rise, concurrent with the rise in prevalence of NAFLD 30 .…”
Section: Discussionmentioning
confidence: 69%
“…We thank Drs Chuah and Chan for their editorial on our study recently published in AP& T 1,2 . We agree that NAFLD and NASH represent a growing disease burden across many countries, with regional differences attributable to several factors.…”
mentioning
confidence: 73%
“…Porphyria cutanea tarda (PCT), the most common type of porphyria, 1,2 is due to decreased activity of hepatic uroporphyrinogen decarboxylase (UROD). A decrease greater than ~80% is necessary for PCT to become clinically manifest with the development of blisters and bullae on areas of skin exposed both to light and trauma, typically the backs of the hands and forearms.…”
Section: Editorial: Hepatitis C and Porphyria Cutanea Tarda In 2020mentioning
confidence: 99%
See 2 more Smart Citations